Road Edge Parking Management Strategy in Semarang City: Collaborative Governance Perspective - Maya Rumantir; Hardi Warsono; Budi Puspo Priyadi; Retno Sunu Astuti; Teuku Afrizal (Budapest International Research and Critics University, 2021)
Roadside parking makes a large contribution to local revenue if managed properly. However, in its implementation, there have been many practices of